Efficacy and safety of Zhishixiaopi decoction in functional dyspepsia: A meta-analysis of randomized controlled trials - Zhao, Xiankun; Cheng, Xinyu; Ye, Jing; Ren, Jiaqing; Li, Bin; Tan, Dongmei; Li, Tangshan; Zhou, Kai; Pu, Jing; Luo, Xia; Feng, Yong (PloS one, 2024)
Functional dyspepsia (FD) refers to a group of clinical symptoms caused by gastric and duodenal dysfunction. Which is a chronic functional disorder of the gastrointestinal tract with no cure. Zhishixiaopi decoction (ZSXP) is a type of Chinese herbal prescription that for treating FD. Although some randomized controlled trials (RCTs) report that ZSXP can significantly improve FD clinical symptoms and/or laboratory results, the trial design varies greatly among studies, making it challenging to draw a conclusion of the efficacy of ZSXP in treating FD. A systematic review and a meta-analysis. Mianyang Central Hospital. We conducted a systematic review and a meta-analysis to evaluate the efficacy and safety of ZSXP for treating FD. We developed inclusion and exclusion criteria based on FD diagnosed criteria, interventions to treat FD, and outcomes of these interventions. Search strategies combined disease terms, symptom terms, anatomy terms and intervention terms. Literature search was conducted on eight online databases in English or Chinese, including Medline (via PubMed), Embase (via Ovid), The Cochrane Library, Web of Science, China Biology Medicine (CBM), China National Knowledge Infrastructure (CNKI), Chinese Scientific Journals Database (VIP), and Wanfang Database. The experimental group received oral administration of ZSXP and had a complete treatment process. ZSXP needs to fully contain the key herbal ingredients, regardless of whether the dosage of each herb is consistent with the original prescription. The Control group received monotherapy or combination therapy of other Western medicine and had a complete treatment process. The primary outcomes appraised were Total effective rate (TER), serum levels of Motilin(MOT), Gastrin(GAS) and Somatostatin (SS), Gastric emptying rate (GER) using a Barium meal method (GER(B)) and Gastric half emptying time using an Ultrasonic method (GHET(T1/2)). The Cochrane Bias Risk Tool was used for quality critical appraisal, Review Manager (RevMan) version 5.3 was used for statistical analysis. A total of 21 medium-quality RCTs were included in the meta-analysis. All 21 included studies were conducted and completed in Mainland China from 1998 to 2020. The treatment duration was between two weeks to two months. The meta-analysis suggests that, compared with the Western medicine treatment group, ZSXP treatment was more effective to improving the TER in FD [Odds ratio, OR = 3.54, 95%CI:(2.49, 5.05), Z = 6.99, P<0.00001] without significant increase in adverse events. However, no statistical significance was found between the groups in serum MOT levels [Standard mean difference, SMD = 1.05, 95%CI:(-0.42, 2.53), Z = 1.04, P = 0.16], serum GAS levels [SMD = -0.16, 95%CI:(-1.20, 0.88), Z = 0.31, P = 0.76], serum SS levels [SMD = -0.04, 95%CI:(-1.97, 1.89), Z = 0.04, P = 0.97], GER(B) [SMD = 1.09, 95%CI:(-0.81, 3.00), Z = 1.12, P = 0.26]or GHET(T1/2) [Mean difference, MD = -2.18, 95%CI:(-5.55, 1.19), Z = 1.27, P = 0.20]. The meta-analysis suggests that Zhishixiaopi treatment is a relatively effective and safe traditional Chinese medicine prescription and could be used for functional dyspepsia treatment. Considering the limitations of this study, the conclusion needs to be further confirmed by high-quality, multi-center, and large-sample randomized controlled trials.